THE IMPACT OF DIGITAL GOVERNANCE REFORMS ON PUBLIC SERVICE DELIVERY IN INDIA: A CASE STUDY OF AADHAAR - Rajendran, Pavankumar (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
This study examines the impact of digital governance reforms on public service delivery in India, with a specific focus on the Aadhaar program. Aadhaar, a unique biometric identification system, has been at the center of India's efforts to streamline public services and improve the efficiency of welfare programs. By providing a universal identification number to over a billion citizens, Aadhaar aims to eliminate redundancies, reduce corruption, and ensure that benefits reach the intended recipients. This paper analyzes the successes and challenges of Aadhaar in transforming public service delivery, drawing on data from government reports, academic studies, and case analyses. The findings indicate that while Aadhaar has significantly enhanced the efficiency and transparency of public services, it has also raised concerns related to privacy, data security, and exclusion of marginalized groups. The study concludes with recommendations for strengthening digital governance in India, emphasizing the need for robust legal frameworks and inclusive policies to maximize the benefits of Aadhaar and similar initiatives.